DEGLACIATION AND REAL PRICE OF TILAPIA FILLETS COMMERCIALIZED IN SÃO CARLOS CITY, SP - MENEGAZZO, C.; FIGUEIREDO, M. A. P.; ROCHA, E. M.; LIRA, N. A. L.; BELO, M. A. A.; MANRIQUE, W. G. (Ars Veterinaria, 2018)
Frozen fish can be stored in freezers for about a year. Glaciation, a stage that occurs after freezing, confers protection and prevents fish oxidation. Studies with fish showed fraud in relation to the glaciation process. In this context, the present research aimed to analyze the amount of glaciation in 81 samples of frozen tilapia fillets of 3 brands, as well as the real price, labeling, packaging integrity, weight and conservation status of these products in 3 supermarket chains in São Carlos-SP, in order to identify frauds. In relation to glaciation, 100% of the samples were in agreement with the current regulatory laws, which stablishes the maximum icing in 20% of the total fish weight, as well as the real prices of each brand and the labels. There were irregularities with the net weights reported on the packages, where 95% of the samples were incompatible with the true weight of the products and only 4.05% were with the effective weights described in the labels. 37.5% of marketing freezers had temperatures above -18°C, which determines the irregularity of the merchant establishment. However, although the glaciation was respected by the three brands, the net weight characterized fraud by the fillet production companies.